Reconstructing concealed cultural remains through integrated geophysical tomographic methods. - Soupios, P.; Papadopoulos, N.; Sarris, A. (Bulletin of the Geological Society of Greece, 2013)
The purpose of this work was to compare the mapping of shallow subsurface archaeological structures through Seismic Refraction Tomography (SRT), Electrical Resistivity Tomography (ERT) and Ground Penetrating Radar (GPR) methods. For achieving the goals of the project, a specific section of the archaeological site in Delphi has been surveyed through the employment of the above techniques. For the SRT survey, twenty four P-wave geophones were installed randomly in a 50 by 40 m area. Totally seventy three (73) shots were made by striking a metal plate with a sledgehammer to collect about 1752 travel-times. The pole-dipole array was employed to capture the ERT data along twenty densely spaced parallel profiles. The GPR data were collected along parallel sections with a resolution of 50 cm between the lines. The SRT and ERT field data were processed with modern tomographic inversion algorithms for the reconstruction of the 3-D velocity and resistivity models describing the buried archaeological remains and the subsurface matrix up to the depth of 5 meters below the ground surface. GPR signals were enhanced with specific filters signifying the shallow structures up to 2 meters below the ground surface. The integrated processing results indicate the existence of walls buried in a relatively uniform background soil. The outcome of this approach signifies that SRT, ERT and GPR methods can be used as a validation tool in any archaeological investigation by providing accurate tomographic subsurface models and contribute in cultural resources management.